The Midnight Lock - Deaver, Jeffery; Ballerini, Edoardo, 1970- ([New York, NY] : Penguin Audio, 2021)
A woman awakes in the morning to find that someone has picked her apartments supposedly impregnable door lock and rearranged personal items, even sitting beside her while she slept. The intrusion, the police learn, is a message to the entire city of carnage to come. Lincoln Rhyme and Amelia Sachs are brought in to investigate and soon learn that the sociopathic intruder, who calls himself "the Locksmith," can break through any lock or security system ever devised. With more victims on the horizon, Rhyme, Sachs and their stable of associates must follow the evidence to the mans lair, and discover his true mission. Their hunt is interrupted when an internal investigation in the police force uncovers what seems to be a crucial mistake in one of Rhymes previous cases. Hes fired as a consultant for the NYPD and must risk jail if he investigates the Locksmith case in secret.
Keywords: Rhyme, Lincoln -- (Fictitious character) -- Fiction; Sachs, Amelia -- (Fictitious character) -- Fiction; Serial murder investigation -- Fiction; Forensic pathologists -- Fiction; Forensic scientists -- Fiction; Locksmiths -- Fiction; Burglars -- Fiction; Serial murderers -- Fiction; Quadriplegics -- Fiction; Police -- New York (State); New York; Fiction; New York (N.Y.) -- Fiction; Sound recording